Interdependence design principles in practice - Vignati, Micael; Johnson, Matthew; Bunch, Larry; Carff, John; Duran, Daniel (Frontiers in Physics, 2022)
Adaptability lies at the heart of effective teams and it is through management of interdependence that teams are able to adapt. This makes interdependence a critical factor of human-machine teams. Nevertheless, engineers building human-machine systems still rely on the same tools and techniques used to build individual behaviors which were never designed to address the complexity that stems from interdependence in joint activity. Many engineering approaches lack any systematic rigor and formal method for identifying, managing and exploiting interdependence, which forces ad hoc solutions or workarounds. This gap between theories of interdependence and operable tooling leaves designers blind to the issues and consequences of failing to adequately address interdependence within human-machine teams. In this article, we propose an approach to operationalizing core concepts needed to address interdependence in support of adaptive teamwork. We describe a formalized structure, joint activity graphs, built on interdependence design principles to capture the essence of joint activity. We describe the runtime requirements needed to dynamically exploit joint activity graphs and to support intelligent coordination during execution. We demonstrate the effectiveness of such a structure at supporting adaptability using the Capture-the-Flag domain with heterogeneous teams of unmanned aerial vehicles and unmanned ground systems. In this dynamic adversarial domain, we show how agents can make use of the information provided by joint activity graphs to generally and pragmatically react and adapt to perturbations in the joint activity, the environment, or the team and explicitly manage and exploit interdependence to produce effective teamwork. In doing so, we demonstrate how flexible and adaptive teamwork can be achieved through formally guided design that supports effective management of interdependence.